Characteristics of two-phase gas-particle flows in circular pipes and bends - Heng, Jinliang (2018)
Pneumatic conveying systems are employed across different industries with its routing flexibility being one of the reasons it is favoured over other systems. In pneumatic conveying, material fed into the system at the inlet goes through a series of closed piping in a very clean operation. However, the use of pipe bends for routing can cause a phenomenon called particle roping which may decrease the overall efficiency of the system. Due to inertial forces acting on the conveyed material about a bend, the material tends to cluster into a rope which decreases its travel velocity. Such phenomena can be studied through experiments and numerical simulations to develop ways to mitigate its detrimental effects. However, in the case of industrial scale pipelines already in operation, such pipelines are often optically opaque and runs for hundreds of metres at one time. Experimental observations of the flow characteristics within the pipeline are impossible. By employing numerical simulations, the cement conveying throughput of 500 tonnes per hour is well matched. The carrier gas is also matched at 12,000 3/ℎ . The flow characteristics from the simulation results such as velocity and pressure drop are replicated to within ±10% of values calculated from empirical formulas. With the results, much more insights can be gained on the flow characteristics. In particular, the region after a vertical-tohorizontal pipe bend displays a sloshing flow characteristic. This is primarily caused by the presence of another horizontal-to-vertical bend at close proximity upstream. This combination of bends results in a flow characteristic that is much different from a single pipe bend flow. Literature regarding the flow characteristics in pipelines with a combination of bends is sparse. Therefore, by employing numerical simulations, the sloshing characteristics can be documented in detail for different cases. By varying the bend radius and the length of the vertical pipe connecting the two bends, different flow characteristics can be observed. Varying the bend ratio (BR) ranging from 2.5 to 25, three classifications of flow characteristic can be seen. The particle rope either has sufficient inertia to make complete loops along the walls of the pipe wall (BR ≲ 2.5) or insufficient inertia to do so; and either splits up into two ropes before merging back at the bottom of the pipe (5 ≲ BR ≲ 10) or disperses within the bend and later on forms again at the bottom of the pipe due to gravity effects (BR ≲14). Next, the connecting length is varied from 0 to 20 times the pipe diameter. It is found that the connecting length has a lesser effect on the particle rope compared to the bend ratio. A longer connecting length facilitates the dispersion of the particle rope formed from the previous bend. In the longest connecting length test case, results from the numerical simulation are able to shed light on the oscillating dispersion characteristics of a particle rope in a vertical pipe. In all, this study is able to shed light on the flow characteristics in an industrial pipeline that which the results could be used to further increase the operating efficiency. Also, the knowledge on the effects of a combination of pipe bends in close proximity is expanded for the current pipeline layout studied. Though, more future studies are needed to completely characterise the effects of a combination of bends in other orientations.